Insight Into the Metabolic Adaptations of Electrically Pulse-Stimulated Human Myotubes Using Global Analysis of the Transcriptome and Proteome - Mengeste, Abel M.; Nikolić, Nataša; Dalmao Fernandez, Andrea; Feng, Yuan Z.; Nyman, Tuula A.; Kersten, Sander; Haugen, Fred; Kase, Eili Tranheim; Aas, Vigdis; Rustan, Arild C.; Thoresen, G. Hege (Frontiers in Physiology, 2022)
Electrical pulse stimulation (EPS) has proven to be a useful tool to interrogate cell-specific responses to muscle contraction. In the present study, we aimed to uncover networks of signaling pathways and regulatory molecules responsible for the metabolic effects of exercise in human skeletal muscle cells exposed to chronic EPS. Differentiated myotubes from young male subjects were exposed to EPS protocol 1 (i.e. 2 ms, 10 V, and 0.1 Hz for 24 h), whereas myotubes from middle-aged women and men were exposed to protocol 2 (i.e. 2 ms, 30 V, and 1 Hz for 48 h). Fuel handling as well as the transcriptome, cellular proteome, and secreted proteins of EPS-treated myotubes from young male subjects were analyzed using a combination of high-throughput RNA sequencing, high-resolution liquid chromatography- tandem mass spectrometry, oxidation assay, and immunoblotting. The data showed that oxidative metabolism was enhanced in EPS-exposed myotubes from young male subjects. Moreover, a total of 81 differentially regulated proteins and 952 differentially expressed genes (DEGs) were observed in these cells after EPS protocol 1. We also found 61 overlapping genes while comparing the DEGs to mRNA expression in myotubes from the middle-aged group exposed to protocol 2, assessed by microarray. Among these DEGs was a myokine, leukemia inhibitory factor, which showed to enhance the glucose uptake in myotubes, indicating a possible autocrine mechanism to maintain metabolic homeostasis. Gene ontology (GO) analysis indicated that significantly regulated proteins and genes were enriched in biological processes related to glycolytic pathways, positive regulation of fatty acid oxidation, and oxidative phosphorylation, as well as muscle contraction, autophagy/mitophagy, and oxidative stress. Additionally, proteomic identification of secreted proteins revealed extracellular levels of 137 proteins were changed in myotubes from young male subjects exposed to EPS protocol 1. Selected putative myokines were measured using ELISA or multiplex assay to validate the results. Collectively, our data provide new insight into the transcriptome, proteome, and secreted proteins alterations following in vitro exercise and is a valuable resource for understanding the molecular mechanisms and regulatory molecules mediating the beneficial metabolic effects of exercise.